Mahmood Mamdani, "South Sudan: The Road to Civil War" Twitter Storify export - Strauber, Chris (Tufts Archival Research Center, 2017)
PDF export of a Storify created from tweets sent during Mahmood Mamdani's lecture "South Sudan: The Road to Civil War" delievered as part of the Melon Sawyer Seminar in Global Humanities.